Medieval World: Vol. 4 (Danbury, CT Grolier Educational, 2001)
Tells the stories of the individuals, peoples, battles, treaties, empires, ideas, and religions that shaped the period we call the Middle Ages.
Keywords: Middle Ages; Civilization, Medieval